Social work in malignant hematological diseases - Ancevska, Zaklina (Ревија за социјална политика/Journal of Social Policy, 2015)
Social Work in health began in 1900 at Massachusetts General Hospital in the US. At that time the way of treating patients where previously the home care has been dominant, progressively started to change to the gradual approximation of hospital treatment. Simultaneously with the changing of the site of treatment i.e. care, the professionals were beginning to understand that the conditions in which the patients lived and their personal problems are one of the factors for their illness and recovery. In that same hospital center, starts a home visiting program to patients by medical students and interns, so they could have the opportunity to know the patients, the way they live and in which conditions they live in.